Pelatihan Penggunaan Aplikasi Pendukung Publikasi Karya Tulis Ilmiah untuk Peningkatan Kompetensi Guru Kimia Sekolah Menengah Umum di Kabupaten Kubu Raya - Andi Hairil Alimuddin; Endah Sayekti; Gusrizal Gusrizal; Ajuk Sapar; Rudiyansyah Rudiyansyah; Titin Anita Zahara; anis shofiyani; Nelly Wahyuni; Thamrin Usman; Risa Nofiani; Ari Widiyantoro; Agus Wibowo; Warsi Kurnia Rahayu; Yoga Pratama; Titik Lestari; Tria Susanti; Tariz Zharfan ME; Aderiya Munika (KOMUNITA: Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2026)
A workshop on the use of supporting applications for the publication of scientific papers has been carried out for Chemistry subject teachers. This activity is in collaboration with the Chemistry Subject Teachers' Conference (MGMP) of Kubu Raya Senior High Schools. This activity aims to utilize the application for compiling bibliographies and checking the similarity of scientific papers to facilitate the writing and publication of scientific papers. The method of implementing the Community Service (PKM) program is through: structural, participatory and instructional approaches; demonstration; practice and mentoring, and evaluation. The results obtained in the form of implementing a one-day workshop activity by presenting research method materials, library search tips and utilization of the Mendeley application, plagiarism checking applications and tips for avoiding plagiarism.The workshop was conducted in the form of a presentation and direct practice of using the application. In addition to being accompanied by the presenters, participants are also accompanied by instructors who have been prepared by the committee so that the activity can run smoothly. In order to increase the interest and attention of participants to participate in the activity, the organizing committee provides door prizes for participants who ask and answer quizzes from the presenters. This method can also be used as an evaluation of the level of understanding of participants in addition to the evaluation in the form of questionnaires distributed after the activity to measure the success of this PKM activity. Based on the questionnaires distributed, participants thought that this activity was very helpful in compiling scientific papers so that it was very useful for participants. Most participants considered that the facilities and training time were in accordance with those conveyed by the presenters who were in accordance with their fields. Overall, it can be concluded that the objectives of implementing this PKM have been achieved.